2010
DOI: 10.1161/circimaging.109.855510
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Diastolic Function in Type 2 Diabetes Mellitus

Abstract: Background-Although type 2 diabetes mellitus is a risk factor for developing congestive heart failure, the mechanism leading to heart failure is unclear. We examined the prevalence of left ventricular (LV) systolic and diastolic dysfunction in patients with type 2 diabetes mellitus in relation to vascular function and myocardial perfusion. Methods and Results-A prospective observational study of 305 patients with type 2 diabetes mellitus (diabetes duration, 4.5Ϯ5.3 years) referred consecutively to a diabetes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(45 citation statements)
references
References 29 publications
(26 reference statements)
6
37
0
2
Order By: Relevance
“…6,7,14 This is not restricted to type 2 diabetes, and we have previously reported a high prevalence of diastolic dysfunction in patients with type 1 diabetes without known heart disease, in which similar sex differences were found. 19 In type 2 diabetes, however, small-sized populations have reported considerable variation in the prevalence of diastolic dysfunction, ranging from 40% to 75%.…”
Section: Prevalence Of Systolic and Diastolic Dysfunction In Patientssupporting
confidence: 54%
See 1 more Smart Citation
“…6,7,14 This is not restricted to type 2 diabetes, and we have previously reported a high prevalence of diastolic dysfunction in patients with type 1 diabetes without known heart disease, in which similar sex differences were found. 19 In type 2 diabetes, however, small-sized populations have reported considerable variation in the prevalence of diastolic dysfunction, ranging from 40% to 75%.…”
Section: Prevalence Of Systolic and Diastolic Dysfunction In Patientssupporting
confidence: 54%
“…4,6,7 In addition, because of advancing age and comorbidities, including hypertension and obesity, patients with type 2 diabetes are also prone to other cardiac pathologies affecting prognosis including but not limited to left ventricular hypertrophy, 8,9 reduced left and right ventricular ejection fraction, 10 dilated left atrium 11 or valve disorders. 12 However, previous reports on prevalence of echocardiographic findings were based on populations that were Abnormal echocardiography in patients with type 2 diabetes and relation to symptoms and clinical characteristics either small 6,7,13,14 from the primary care setting/general population 4,15,16 or included patients before the era of modern multifactorial treatment. 17 Even more, contemporary, intensive treatment of hypertension, hyperglycaemia, dyslipidemia and lifestyle factors 18 may have changed the risk profile for having echocardiographic abnormalities making it difficult to choose which patients to refer to echocardiography.…”
Section: Introductionmentioning
confidence: 99%
“…We also found associations between plasma fibulin-1 concentrations and signs of myocardial dysfunction, when judged in relation to left atrial volume index and plasma concentrations of NT-proBNP. The most likely cause of variation in left atrium volume in this study is pressure overload caused by abnormal left ventricular relaxation, known to be present in our diabetic population (23 ). This overload may at least partly be caused by increased arterial stiffness, which leads to premature return of reflected pulse waves in late systole (34,37,38 ).…”
Section: Discussionmentioning
confidence: 75%
“…Echocardiograms were obtained and stored digitally for subsequent blinded analysis as described previously (23 ) and as summarized in the online Supplemental Data file. Similarly, B-mode ultrasound of the carotid artery was performed (24 ) as described in the online Supplemental Data file.…”
Section: Echocardiography Carotid Intima-media Thickness and Complimentioning
confidence: 99%
“…In present study, the prevalence of diastolic dysfunction was 54.33%. Poulsen et al 41 in their prospective observational study of 305 patients with type 2 DM showed that abnormal LV filling is closely associated with abnormal myocardial perfusion on myocardial perfusion scintigraphy.…”
Section: Discussionmentioning
confidence: 99%